Binapthyl Schiff base diamine complex covalently bonded to modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Singh, A. P. (Catalysis Today, 2012)
Protected mesoporous SBA-15 phase was synthesized by grafting the complex Chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) through the reactive 3-aminopropyl trimethoxysilane(3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques like elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, XPS, and solid state C-13 NMR. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done for the oxidation reaction of thioanisole (methyl phenyl sulfide) using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and exhibit enantiomeric excess comparable to homogeneous catalyst. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: -OH protected NH2-SBA-15; Binaphthyl Schiff base ligand; Ordered mesoporous materials; Sulfoxidation; Thioanisole

Mn(III) based binapthyl schiff base complex hetrogenized over organo-modified SBA-15: synthesis, characterization and catalytic application - Sharma, Priti; Lazar, Anish; Singh, A. P. (Applied Catalysis A-General, 2012)
A heterogenized organocatalyst was synthesized by the covalent anchoring; of the complex chloro (S,S)(-)[N-3-tert-butyl-5-chloromethyl salicylidene]-N'-[3',5'-di-tert-butyl salicylidene] 1,1'-binapthyl-2,2'-diamine manganese(III) over modified mesoporous surface of SBA-15 through the reactive 3-aminopropyl trimethoxysilane (3-APTMS) group. The surface properties of the functionalized catalyst were analyzed by a series of characterization techniques such as elemental analysis, XRD, N-2 sorption measurement isotherm, FT-IR, TGA-DTA, XPS, and solid state C-13 NMR. The XRD and N-2 sorption measurement, UV reflectance and CP MAS NMR spectroscopy (C-13 and Si-29) of the catalyst confirmed the structural integrity of the mesoporous hosts and the spectroscopic characterization technique proved the successful anchoring of the metal complex over the modified mesoporous support. The screening of the catalyst Mn(III)-L-SBA-15 and neat Mn(III)-L complexes was done in the oxidation reaction of thioanisole (methyl phenyl sulfide) by using TBHP as an oxidant. Mn(III)-L-SBA-15 catalyst shows higher activities and turnover number (TON) and exhibit enhanced enantiomeric excess comparable to homogeneous catalyst [Mn(III)-L]. [Mn(III)-L-SBA-15] catalyst was found more active than homogeneous catalyst [Mn(III)-L]; Moreover bulkier alkene like 1,2-dihydronapthalene was also efficiently epoxidised with the synthesized supported catalyst. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Binaphthyl ligand; Chiral Schiff-base; Immobilization; Post grafting synthesis

Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Covalently anchored 2,4,6-triallyloxy-1,3,5-triazine Pd(II) complex over a modified surface of SBA-15: catalytic application in hydrogenation reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
Highly efficient and reusable SBA-15-TAT-Pd(II) has been synthesized by anchoring a 2,4,6-triallyloxy-1,3,5-triazine (TAT) complex over the organo-functionalized surface of SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherm, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, DRS UV-visible, SEM and TEM. XRD & N-2 sorption were analyzed to find out the textural properties of the synthesized catalyst and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The electronic environment and oxidation state of Pd in SBA-15-TAT-Pd(II) were monitored by XPS and DRS UV-visible techniques. The catalytic activity of the synthesized catalyst SBA-15-TAT-Pd(II) was screened for hydrogenation reactions and shows higher catalytic activity with good turnover numbers (TON) under optimized experimental conditions with maximum conversion (> 99%) and selectivity (100%). The anchored solid catalyst can be recycled efficiently and reused upto five times without major loss in reactivity.

Phosphine free SBA-15-EDTA-Pd highly active recyclable catalyst: synthesis characterization and application for suzuki and sonogashira reaction - Sharma, Priti; Singh, A. P. (Catalysis Science & Technology, 2014)
Phosphine obstructed highly efficient and reusable SBA-15-EDTA-Pd(11) has been synthesized by anchoring a Pd-EDTA complex over the surface of organo-functionalized SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherms, TGA and DTA, solid state C-13, Si-29 NMR spectroscopy FT-IR, XPS DRS UV-visible, SEM and TEM. The XRD and N-2 sorption analyses of the synthesized catalyst confirm that the ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide a good structural stability, an the existence of a long range order and high pore wall thickness. The TGA-DTA results reveal that the thermal stability of the synthesized catalyst SBA-15-EDTA-Pd(11) was maintained at higher temperature. The organic moieties anchored over the surface of the SBA-15 and inside the pore wall were demonstrated by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides information about the degree of functionalization of the surface silanol groups, of the SBA-15 with organic moieties. The electronic environment and oxidation state of the Pd metal in the SBA-15-EDTA-Pd(11) were monitored by XPS, and DRS UV-visible techniques. Moreover, the morphologies and topographic information of the synthesized catalyst were confirmed by SEM and TEM spectroscopy. The synthesized catalyst SBA-15-EDTA-Pd(11) was screened for the Suzuki and Sonogashira coupling reactions and shows a higher catalytic activity with higher TON (turn over number). The anchored solid catalyst can be recycled efficiently and reused five times, without a major loss in the reactivity.

Synthesis of a recyclable and efficient Pd(II) 4-(2-pyridyl)-1,2,3-triazole complex over a solid periodic mesoporous organosilica support by ``click reactions'' for the stille coupling reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
A highly efficient, reusable B-PMO-TZ-Pd(II) catalyst was synthesized by anchoring 4-(2-pyridyl)-4-(2-pyridyl)-1,2,3-triazole ligand over the surface of an organo-functionalized benzene support containing periodic mesoporous organosilica (B-PMO) via ``click reaction'' and the subsequent complexation with PdCl2. B-PMO materials with uniform hexagonal arrangements were prepared using C-16 alkyl trimethyl ammonium bromide [CTAB] surfactant under basic conditions. The physiochemical properties of the functionalised catalyst were analysed by elemental analysis, ICP-OES, XRD, N-2 sorption, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, UV-vis, SEM and TEM. XRD and N-2 sorption revealed the morphological and textural properties of the synthesized catalyst, confirming that ordered mesoporous channel structure was retained even after the multistep synthetic procedure. The (100), (110) and (200) reflections in B-PMO are evidence of its good structural stability and the existence of long range order. The TGA-DTA results reveal that the synthesized catalyst B-PMO-TZ-Pd(II) was thermally stable, even at high temperature. The organic moieties anchored over the surface of B-PMO were demonstrated by solid state C-13 NMR and FT-IR spectroscopy. Solid state Si-29 NMR spectroscopy provides information about the degree of functionalization of the surface silanol group. The electronic environment and oxidation state of Pd in B-PMO-TZ-Pd(II) were monitored by XPS and UV-visible techniques. Moreover, the morphologies and topographic information of the synthesized B-PMO-TZ-Pd(II) catalyst were confirmed by SEM and TEM analyses. The catalytic properties of the catalyst for the Stille coupling reaction were screened, and higher catalytic activities with high TONs were observed. The anchored solid B-PMO-TZ-Pd(II) catalyst can be recycled efficiently and reused several (four) times without a major loss in reactivity.

Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki

Synthesis and characterization of nanoporous silica SBA-15 diaminocyclohexane and its application in removal of Cu(II) and Ni(II) from aqueous solution - Sreenu, Bhogineni; Sharma, Priti; Seshaiah, Kalluru; Singh, A. P. (Desalination and Water Treatment, 2016)
A new nanoporous 1,2-diaminocyclohexane-functionalized SBA-15 (Dach@SBA-15) silica sorbent was prepared. The structure and physicochemical properties of the material were characterized by elemental analysis, X-ray diffraction, transmission electron microscopy (TEM), scanning electron microscopy, FT-IR spectroscopy, nitrogen adsorption-desorption isotherms and thermogravimetric analysis. TEM image clearly showed the sheet-like structure of Dach@SBA-15. The organic functional groups were successfully grafted onto the SBA-15 surface and the ordering of the support was not affected by the chemical modification. The Dach@SBA-15was used as a sorbent for removal of Cu(II) and Ni(II) from aqueous solution. Experimental parameters like effect of pH, contact time and metal ion concentration were studied and optimized. The adsorption isotherm data fitted well to Langmuir isotherm model and the monolayer adsorption capacity values for Cu(II) was 90.09 and for Ni (II) was 84.03 mg/g at 303 K. The experimental kinetic data fitted very well to the pseudosecond- order model. The Dach@SBA-15 could be used as a sorbent for removal of Cu(II) and Ni(II) from aqueous medium.
Keywords: Adsorption; BET; FAAS; FT-IR; Heavy metals; Nanoporous silica

Synthesis of new hybrid sorbent 2-mercaptobenzaldehyde SBA-15 and its application in solid phase extraction of Cd(II) from water and food samples - Sreenu, B.; Imran, K.; Seshaiah, K.; Sharma, Priti; Singh, A. P. (Analytical Methods, 2016)
In this paper, a new mesoporous hybrid material was fabricated by anchoring 2-mercaptobenzaldehyde (2MB) onto the surface of SBA-15. The adsorbent (2MB-SBA-15) was characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), nitrogen adsorption-desorption isotherm measurements and thermogravimetric analysis (TGA) and applied as a sorbent in the preconcentration of Cd(II) in water samples and food samples. The effect of various analytical parameters such as pH, dose of sorbent, amount of eluent, sample flow rate and interfering ions was investigated. The preconcentration capacity of the prepared material under optimized conditions for Cd(II) was 0.94 +/- 0.01 mmol g(-1). The Cd collected onto the sorbent was eluted out with 10 mL of 1 M HNO3 and determined by AAS. The LOD, LOQ and preconcentration factor of the present method were found to be 6.93 x 10(-6), 1.21 x 10(-5) mM and 100, respectively. The relative standard deviation for four preconcentration experiments was found to be <= 5%.

Highly active recyclable SBA-15-EDTA-Pd catalyst for Mizoroki-Heck, Stille and Kumada C-C coupling reactions - Rathod, Jayant; Sharma, Priti; Pandey, Punam; Singh, A. P.; Kumar, Pradeep (Journal of Porous Materials, 2017)
Highly efficient SBA-15-EDTA-Pd(11) heterogeneous catalyst was synthesized by covalent anchoring Pd-EDTA complex over organo-modified surface of SBA-15. SBA-15-EDTA-Pd(11) catalyst was found to exhibit excellent catalytic activity in appreciable yield for Heck, Stille and Kumada cross-coupling reactions. Catalytic system exhibited excellent activity for completion of reaction, isolation, Pd loading (0.87 mmol%) and yields of products as compared to earlier reported heterogeneous supported Pd catalysts. Covalently anchored heterogeneous SBA-15-EDTA-Pd(11) catalyst can be recycled for more than five times without noticeable loss in activity and selectivity.

Synthesis of heterogeneous Ru(II)-1,2,3-triazole catalyst supported over SBA-15: application to the hydrogen transfer reaction and unusual highly selective 1,4-disubstituted triazole formation via multicomponent click reaction - Sharma, Priti; Rathod, Jayant; Singh, A. P.; Kumar, Pradeep; Sasson, Yoel (Catalysis Science & Technology, 2018)
In the present study, we demonstrate a simple and efficient method for ligand formation and covalent anchoring to a heterogeneous support via click reaction. The complex tris(triphenylphosphine) ruthenium(II) dichloride [RuCl2(PPh3)(3)] anchored over the click modified ligand of SBA-15 forms a new highly efficient heterogeneous SBA-15-Tz-Ru(II) TPP catalyst. Solid state C-13, Si-29, and P-31 CP-MAS NMR spectra provide evidence for the formation of the heterogeneous catalyst. SBA-15-Tz-Ru(II) TPP catalyst was screened for the multicomponent click cycloaddition reaction in water medium as a green solvent and it exhibited unusual and excellent selectivity for the formation of 1,4-disubstituted triazole product under mild reaction condition. In addition, SBA-15-Tz-Ru(II) TPP catalyst also catalyzed the hydrogen transfer reaction of various carbonyl compounds with excellent catalytic activity to give the corresponding alcohols. The heterogeneous catalyst can be recycled and reused several times (five) without a loss in reactivity.